The Role of the Constitutional court in Development of the Italian and Serbian Constitutional Systems - Rajić, Nataša; Орловић, Слободан (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Constitutional court, as special institution of the centralised system of constitutional control, takes significant place in modern constitutional state. The aim of this paper is to indicate the main features of Italian and Serbian constitutional courts and their role in development of constitutional systems. The analysis will cover the scope and quality of their competences, the way that they use to interpret the constitutional text and the quality of dialogue that they develop with judicial and political organs. The special focus will be put on the role of the Italian Constitutional court in protection of constitutional identity which seems to have the key role in development of the European constitutionalism today.
Keywords: constitutional court, constitutional system, Italy, Serbia